2014
DOI: 10.1038/nn.3743
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect pathways of basal ganglia: a critical reappraisal

Abstract: The basal ganglia are subcortical nuclei controlling voluntary actions and have been implicated in Parkinson's disease (PD). The prevailing model of basal ganglia function states that two circuits, the direct and indirect pathways, originate from distinct populations of striatal medium spiny neurons (MSNs) and project to different output structures. These circuits are believed to have opposite effects on movement. Specifically, the activity of direct pathway MSNs is postulated to promote movement, whereas the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
587
1
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 659 publications
(617 citation statements)
references
References 98 publications
21
587
1
8
Order By: Relevance
“…In addition, several studies have reported the high density of CB 1 Rs in striatum and the presence of AEA throughout the basal ganglia, in particular in the globus pallidus and substantia nigra [31,57,58]. The crosstalk between dopaminergic transmission and endocannabinoids signaling in the striatum nigra is also well established and there is a growing body of evidence that CB 1 R activation by endocannabinoid retrograde signaling has the potential to decrease glutamate release in a dopaminergic D 2 receptor-dependent manner [59][60][61].…”
Section: Cannabinoid Receptors and Signaling In Relations To Central mentioning
confidence: 99%
“…In addition, several studies have reported the high density of CB 1 Rs in striatum and the presence of AEA throughout the basal ganglia, in particular in the globus pallidus and substantia nigra [31,57,58]. The crosstalk between dopaminergic transmission and endocannabinoids signaling in the striatum nigra is also well established and there is a growing body of evidence that CB 1 R activation by endocannabinoid retrograde signaling has the potential to decrease glutamate release in a dopaminergic D 2 receptor-dependent manner [59][60][61].…”
Section: Cannabinoid Receptors and Signaling In Relations To Central mentioning
confidence: 99%
“…VD 3 RA (only) treatment caused an increase in motor activity in control animals when compared with the control (untreated) animals. Neural recordings for VD 3 RA treatment showed a decline in RMS in the M1 (L4 -L6) coupled with a decreased frequency of the spike train. However, this group recorded a slight decline in CPu RMS when compared with the control (Figure 1(f)).…”
Section: Motor Neural Activity (M1 and Cpu) In -D 2 Induced Dyskinesiamentioning
confidence: 99%
“…Several studies have shown a decline in motor function and cognition after a prolonged use of these drugs in treatment of depression and schizophrenia [7] [8]. Going further, the observed behavioral deficits were attributed, in part, to loss of dopaminergic neurotransmission in the motor and memory neural systems, predominantly due to D 2 R inhibition and abnormal calcium currents in corticostriatal outputs [3] [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased DA levels in the nucleus accumbens shell stimulate the D 1 receptor in the mice treated with methamphetamine (Uno et al, 2017). The D 1 receptor activation induces the increase in cAMP levels, the activation of protein kinase A (PKA), and eventually the phosphorylation of nuclear CREB (Calabresi et al, 2014). If α-PVP has a similar mechanism with methamphetamine, phosphorylation of CREB should be detected.…”
Section: Introductionmentioning
confidence: 99%